The Influence of Academic Supervision of School Heads and Organizational Culture on Teachers Performance - Febriasari, Eni; Fitria, Happy; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine the effect of principal academic supervision and organizational culture on teacher performance. The location of this research was carried out in SD Negeri in Cluster I, Betung District. This type of research is quantitative research with ex post facto research design. The sample in this study were consisting of 55 teachers. The data collection technique used a questionnaire. The data analysis technique used quantitative descriptive techniques and multiple linear regression. The results of the study stated that 1) there was a significant effect of the principal's academic supervision on the performance of public elementary school teachers; 2) there is a significant influence of organizational culture on the performance; 3) there is a significant influence on the academic supervision of the principal and organizational culture together on the performance of SD teachers in Cluster I, Betung District